ANALISIS PERMINTAAN PUPUK PADA USAHATANI PADI DI KABUPATEN LAHAT - Ketut Sukiyono (Jurnal Bisnis Tani, 2021)
The purpose of this study is 1) to determine the amount of fertilizer demand in Lahat District. 2) Analyzing the factors that influence fertilizer demand in Lahat District. The location of this study was determined purposively (Purposive), this study was conducted in the District of South Lahat and Tanjung Sakti Pumi, Lahat Regency, South Sumatra Province. The choice of these two subdistricts is based on the consideration that most farmers in this area have jobs as lowland rice farmers. Taking respondents using simple random sampling method, with a sample size of 160 farmers. The analysis used in this study is Cobb-Douglass type multiple linear regression analysis. The results of the study showed that the average use of UREA fertilizer was 119.09 Kg / Ut or 267.3 Kg / Ha / Mt and TSP fertilizer was 83.81 Kg / Ut or 183.42 Kg / Ha / Mt. The results showed that the factors of land area and seed prices significantly affected the demand for UREA fertilizer in Lahat Regency, while the price of products / rice, UREA fertilizer prices, TSP fertilizer prices and labor wages did not significantly affect the demand for UREA fertilizer in Lahat District. And that the land area factor has a significant effect on the demand for TSP fertilizer in Lahat Regency, while the price of seeds, product / rice prices, UREA fertilizer prices, TSP fertilizer prices and labor wages have no significant effect on TSP fertilizer demand in Lahat District.